ALLOMETRIC SCALING OF WINGATE ANAEROBIC TESTSCORES IN YOUNG SOCCER PLAYERS - Borislava Petrova (Scientific Publishing House. NSA Press, 2018)
In this study, we:(a) developed allometric exponents for scaling Wingate anaerobic test (WAnT) power data that are effective in controlling body mass (BM) influence; and (b) established a normative WAnT data set for young soccer players. Forty-six players completed a standard WAnT. Allometric exponents and percentile ranking for peak power (PP), average power (AP) and power output for 30 s (W 30 s) were established. Allometric exponents "b" for PP, AP and W (30 s) scaled for BM were 0.72,0.78 and 0.85 respectively using braking force 75 g.kg-1, markedly higher from the theoretical suggested of b=0.67. The study shows the possibilities of applying the allometric scaling in the coaches practice. If these exponents in allometric scaling of young soccer players are used, WAnT power values will provide coaches with valid means for comparing power production between individuals without the confounding influence of BM.